Efek Pemanasan Skala Rumah Tangga terhadap Komponen Bioaktif Daun Kenikir (Cosmos caudatus) - Ardiansyah Ardiansyah; Risqah Fadilah; Dody Dwi Handoko; Bram Kusbiantoro; Rizki Maryam Astuti (agriTECH, 2019)
Kenikir leaves (Cosmos caudatus) are one type of vegetable that is commonly consumed in Indonesia both in fresh or cooked forms. The research was aimed to investigate the effect of household scale heating (boiling, steaming, or microwave heating) on the total phenolic content (TPC), antioxidant activity, and bioactive components of kenikir leaves. The research was divided into several stages such as sample preparation, household scale processing method, extraction, TPC analysis by folin-ciocalteu method, antioxidant activity analysis by DPPH method, and bioactive components analysis (caffeic acid and ferulic acid) by a reversed-phase ultra-high-performance liquid chromatography. The TPC of fresh kenikir leaves extract was 148.29–262.36 mg/100 g WB. Boiling or microwave heating for 3 minutes significantly decreased (p<0.05) TPC and antioxidant activity of kenikir leaves, as well as caffeic acid and ferulic acid contents. The steaming or microwave heating for one minute didn’t show significant differences in TPC and antioxidant activity when compared to fresh kenikir leaves. Furthermore, the steaming or microwave heating for one minute could maintain caffeine acid and ferulic acid contents of kenikir leaves. The correlation analysis showed that there was a positive correlation between TPC and antioxidant activity of kenikir leaves (r = 0.904).